Elektrokromni sklop s trdnim redoks-elektrolitom I-/I3-, pripravljenim po postopku sol-gel - Surca, Angelja Kjara (Vakuumist, 2002)
We report on the construction of a hybrid EC device without the counter-electrode with the intercalation properties as in usual battery type of EC devices. This is replaced by the redox pair Isub3sup-&Isup- in the solid sol-gel electrolyte and Pt electrode. The sol-gel electrolyte was prepared from an organic-inorganic ICS-PPG precursor, ethanol, KI and Isub2 and acetic or valeric acids as catalysts for the hydrolysis/condensation reactions. The hybrid EC devices color in 10-20 s, while their coloration efficiencies are between 6 and 10 cmsup2Csup-1. Device functioning was studied with the resonance Raman spectroscopy, focusing the laser with the excitation line of 647 nm on the redox electrolyte encapsulated in the hybrid EC cell. The increase in the relative integral intensity of the simmetric stretching of Isub3sup- ions on the Pt-side of the device was accompanied by the drop in the absolute background intensity. We explained this phenomenon with the dissociation of the KI mocrocrystallites, which formed immediately after the application of the redox electrolyte in the device, because of the intercalation of Ksup+ ions in WOsub3 film.
Keywords: elektrokromizem; elektrokromni materiali; sol-gel postopki